Controllable Synthesis of Upconversion Nanophosphors toward Scale‐Up Productions. (16th August 2020) - Jiao, Yiran; Ling, Chen; Wang, Jie‐Xin; Amanico, Honeyfer; Saczek, Joshua; Wang, Haoyu; Sridhar, Sreepathy; Xu, Ben Bin; Wang, Steven; Wang, Dan
Abstract: Upconversion nanophosphors (UCNPs) are considered as an important synthesis arm within biomedical and energy sectors due to their unique optical characteristics, which can convert near‐infrared light into higher energy emissions. However, key challenges, cost, compatibility of the materials, etc. have to be taken into serious consideration to transform this in‐lab UCNPs technology into scale‐up production for wider commercial needs. This review highlights the fundamental concepts of synthetic approaches for UCNPs and recaps recent advances in terms of large‐scale production. A number of typical synthesis routes in both batch and continuous processes are reviewed, alongside their limitations and potential improvements when being considered for mass production. By discussing and exploiting the technical compacity for the potential synthetic trends, key challenges, and expectations of future synthesis methods for UCNPs are also outlined. Abstract : By reviewing the current advances on the upconversion nanophosphors (UCNPs) synthesis, the potential map for future scale‐up production is holistically outlined, by simplifying the synthesis operation via mitigating the reaction conditions toward a substantially greener synthesis.